Adhesive layer for nonaqueous electrolyte secondary battery
An adhesive layer for nonaqueous electrolyte secondary batteries using flexible chain polymers with carbonyl groups addresses adhesion and heat resistance issues, enhancing the battery's performance and safety.
Patent Information
- Application Number
- JP2023178458
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-28
AI Technical Summary
Existing adhesive layers for nonaqueous electrolyte secondary batteries face challenges in achieving sufficient adhesion while maintaining other essential properties such as heat resistance.
The development of an adhesive layer containing a flexible chain polymer with a carbonyl group in its main chain, specifically semi-aromatic or aliphatic polyamides and polyurethanes, which provides improved adhesion without compromising heat resistance.
The adhesive layer effectively enhances the adhesion between the battery components, ensuring reliable performance and maintaining heat resistance, thus improving the overall efficiency and safety of nonaqueous electrolyte secondary batteries.
Smart Images

Figure 2025068504000002 
Figure 2025068504000003 
Figure 2025068504000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive layer for a non-aqueous electrolyte secondary battery. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries, particularly lithium ion secondary batteries, are widely used as batteries for personal computers, mobile phones, personal digital assistants, and in-vehicle applications due to their high energy density. Lithium ion batteries usually have a separator between the positive electrode and the negative electrode, and various separators have been proposed. For example, Patent Document 1 discloses a separator for secondary batteries in which a first porous layer having a shutdown property and a second porous layer containing an aramid resin and an inorganic material are laminated. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2006-299612 Summary of the Invention [Problem to be solved by the invention]
[0004] The above-mentioned conventional techniques leave room for improvement in adhesion. One aspect of the present invention provides an adhesive layer for a non-aqueous electrolyte secondary battery. [Means for solving the problem]
[0005] The present invention includes the following aspects. <1> An adhesive layer for a non-aqueous electrolyte secondary battery comprising a flexible chain polymer, The flexible chain polymer is a polymer having a carbonyl group in its main chain and a flexible chain in its structure, The flexible chain is a structure that is not entirely aromatic. Adhesive layer for non-aqueous electrolyte secondary batteries. <2> the carbonyl group is contained in any one or more of the group consisting of an amide bond, an ester bond, an imide bond, a urethane bond, and a urea bond; <1> The adhesive layer for a non-aqueous electrolyte secondary battery according to claim 1. <3> The flexible chain polymer is any one or more of the group consisting of semi-aromatic polyamide, aliphatic polyamide, semi-aromatic polyurea, aliphatic polyurea, semi-aromatic polyurethane, and aliphatic polyurethane; <1> or <2> The adhesive layer for a non-aqueous electrolyte secondary battery according to claim 1. <4> The flexible chain polymer is present in an amount of 20 to 100% by weight, with the total weight of the resin contained in the adhesive layer being 100% by weight. <1> ~ <3> 10. An adhesive layer for a non-aqueous electrolyte secondary battery according to claim 9. <5> Further comprising a heat-resistant resin, <1> ~ <4> 10. An adhesive layer for a non-aqueous electrolyte secondary battery according to claim 9. <6> A polyolefin porous film has a heat-resistant layer on one or both sides thereof, and further has a surface of the heat-resistant layer that is not in contact with the polyolefin porous film. <1> ~ <5> 1. A laminate separator for a non-aqueous electrolyte secondary battery, comprising the adhesive layer for a non-aqueous electrolyte secondary battery according to claim 1 laminated thereon. <7> On one or both sides of the polyolefin porous film, <1> ~ <5> 1. A laminate separator for a non-aqueous electrolyte secondary battery, comprising the adhesive layer for a non-aqueous electrolyte secondary battery according to claim 1 laminated thereon. <8> A positive electrode and <1> ~ <5> An adhesive layer for a non-aqueous electrolyte secondary battery according to any one of the above items, A negative electrode; The above are laminated in this order. <9> A positive electrode and <6> The laminate separator for a nonaqueous electrolyte secondary battery according to claim 1, A negative electrode; The above are laminated in this order. <10> A positive electrode and <7> The laminate separator for a nonaqueous electrolyte secondary battery according to claim 1, A negative electrode; The above are laminated in this order. <11> <1> ~ <5> The adhesive layer for a non-aqueous electrolyte secondary battery according to any one of the above items. <6> or <7> The laminate separator for a non-aqueous electrolyte secondary battery according to claim 1, <8> ~ <10> 13. A non-aqueous electrolyte secondary battery comprising the member for a non-aqueous electrolyte secondary battery according to claim 12. Effect of the Invention
[0006] According to one aspect of the present invention, an adhesive layer for a non-aqueous electrolyte secondary battery is provided. [Brief description of the drawings]
[0007] [Figure 1] 1 is a schematic diagram showing an example of a general structure of a laminate separator according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic diagram showing an example of a general structure of a laminate separator according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, the embodiments of the present invention will be described in detail. However, the present invention is not limited to this, and various modifications are possible within the scope described, and embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. In addition, unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more, B or less."
[0009] [1. Adhesive layer for nonaqueous electrolyte secondary batteries] The adhesive layer for non-aqueous electrolyte secondary batteries according to one embodiment of the present invention is an adhesive layer for non-aqueous electrolyte secondary batteries that includes a flexible chain polymer. In this specification, the "adhesive layer for non-aqueous electrolyte secondary batteries" is also simply referred to as an "adhesive layer". Here, the flexible chain polymer is a polymer having a carbonyl group in the main chain. The carbonyl group may be included in one or more bonds selected from the group consisting of, for example, an amide bond, an ester bond, an imide bond, a urethane bond, and a urea bond.
[0010] A flexible chain polymer is a polymer having a flexible chain in its structure. Here, a flexible chain is a structure that is not fully aromatic. In this specification, "fully aromatic" includes a structure consisting of only aromatic rings connected by bonds containing heteroatoms. Flexible chain structures include semi-aromatic polyamides, aliphatic polyamides, semi-aromatic polyureas, aliphatic polyureas, semi-aromatic polyurethanes, and aliphatic polyurethanes. In this specification, "semi-aromatic" includes a structure consisting of a monomer having an aromatic ring and a monomer not having an aromatic ring. In this specification, "aliphatic" includes a structure consisting of only a monomer not having an aromatic ring.
[0011] In this specification, the term "aromatic ring" refers to a cyclic compound that satisfies the Huckel rule. Examples of aromatic rings include benzene, naphthalene, anthracene, azulene, pyrrole, pyridine, furan, and thiophene. In one embodiment of the present invention, the aromatic ring is composed of only carbon atoms and hydrogen atoms. In one embodiment of the present invention, the aromatic ring is a benzene ring or a condensed ring of two or more benzene rings (such as naphthalene and anthracene).
[0012] The aromatic ring may have a substituent, and examples of the substituent include an alkyl group, an alkenyl group, an alkynyl group, a cycloalkyl group, a cycloalkenyl group, a cycloalkynyl group, a hydroxyl group, a carboxyl group, a nitro group, an amino group, a halogen group, and a sulfonic acid group. When the substituent has a carbon atom, the number of carbon atoms contained in one substituent may be 1 to 20, 1 to 15, or 1 to 10.
[0013] In order to give flexibility to the polymer chain, it is preferable that the amount of aromatic rings contained in the main chain is small. In one embodiment, when the total units constituting the flexible chain polymer are 100 mol%, the ratio of units containing aromatic rings in the main chain is preferably 70 mol% or less, more preferably 60 mol% or less, and even more preferably 50 mol% or less. In one embodiment, the flexible chain polymer does not have an aromatic ring in the main chain.
[0014] Examples of monomers that do not have an aromatic ring and that constitute flexible chain polymers include diamines in which two amino groups are bonded by a hydrocarbon chain (trimethylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, etc.); diamines in which two amino groups are bonded by a polyether (1,2-bis(2-aminoethoxy)ethane, 1,3-bis(3-aminopropoxy)ethane, etc.); and dicarboxylic acid halides in which two carboxylic acid halide groups are bonded by a hydrocarbon chain (succinic acid dichloride, glutaric acid dichloride, adipic acid dichloride, pimelic acid dichloride, suberic acid dichloride, azelaic acid dichloride, sebacic acid dichloride, etc.). diisocyanates in which two carboxylic acid halide groups are linked by a polyether; diisocyanates in which two isocyanate groups are linked by a hydrocarbon chain (e.g., trimethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, heptamethylene diisocyanate, octamethylene diisocyanate, 1,6-diisocyanato-2,4-dimethylhexane, 1,9-diisocyanato-5-methylnonane, etc.); diisocyanates in which two isocyanate groups are linked by a polyether (e.g., 1,10-dioxa-4,7-dioxa-2,9-diazadeca-1,9-diene, 1,2-bis(3-isocyanatopropyloxy)propane, etc.).
[0015] The lower limit of the content of the flexible chain polymer is preferably 20% by weight or more, more preferably 40% by weight or more, based on the total weight of the resin contained in the adhesive layer being 100% by weight. The upper limit of the content of the flexible chain polymer may be, for example, 100% by weight, based on the total weight of the resin contained in the adhesive layer being 100% by weight. If the content of the flexible chain polymer is within the above range, the adhesive layer can have sufficient adhesiveness.
[0016] The adhesive layer may contain a mixture of a flexible chain polymer and a heat-resistant resin. Examples of the heat-resistant resin include fully aromatic polyamides (aramid resins). An adhesive layer containing such a mixture is referred to herein as a "heat-resistant adhesive layer."
[0017] Alternatively, the adhesive layer may not contain a heat-resistant resin and may be a layer mainly composed of a flexible chain polymer. Such an adhesive layer is referred to as a "simple adhesive layer" in this specification. For example, a simple adhesive layer may be laminated on a heat-resistant layer.
[0018] A layer containing a flexible polymer as a resin component in this way exhibits adhesiveness and functions as an adhesive layer. Such adhesiveness is not observed in a layer containing only a heat-resistant resin (such as a wholly aromatic polyamide) as a resin component. However, the adhesive layer may have a function other than adhesiveness (such as heat resistance). For example, the adhesive layer may also be a heat-resistant layer at the same time.
[0019] In one embodiment, the adhesive layer may include a filler. Examples of the filler include organic fillers and inorganic fillers. Among these, inorganic fillers are preferred.
[0020] The inorganic filler is preferably made of one or more inorganic oxides selected from the group consisting of silica, calcium oxide, magnesium oxide, titanium oxide, alumina, mica, zeolite, aluminum hydroxide, boehmite, etc. In order to improve the water absorption of the inorganic filler, the surface of the inorganic filler may be subjected to a hydrophilic treatment with a silane coupling agent, etc.
[0021] The upper limit of the particle size of the inorganic filler contained in the adhesive layer is preferably 1.0 μm or less, and more preferably 0.8 μm or less, from the viewpoint of making it possible to reduce the thickness of the laminated separator, and the lower limit of the particle size of the inorganic filler in the adhesive layer is preferably 0.005 μm or more, and more preferably 0.010 μm or more, from the viewpoint of making it possible to form the pore structure of the laminated separator.
[0022] Here, the average particle size of the inorganic filler is the average value of the equivalent sphere particle size of 50 inorganic fillers. The equivalent sphere particle size of the inorganic filler is a value actually measured by a transmission electron microscope. An example of a specific measurement method is as follows. 1. Using a transmission electron microscope (TEM; JEOL Ltd., JEM-2100F), images were taken at an accelerating voltage of 200 kV and a magnification of 10,000x using a Gatan Imaging Filter. 2. Using image analysis software (ImageJ), trace the particle contours of the obtained images and measure the spherical equivalent particle size of the inorganic filler particles (primary particles). 3. The above measurement is carried out on 50 randomly selected inorganic filler particles. The arithmetic mean of the spherical equivalent diameters of the 50 inorganic filler particles is taken as the average particle diameter of the particles.
[0023] The upper limit of the inorganic filler content in the adhesive layer is 70% by weight or less, preferably 65% by weight or less, more preferably 60% by weight or less, and even more preferably 55% by weight or less, when the total weight of the adhesive layer is 100% by weight. If the inorganic filler content is 70% by weight or less, the occurrence of mutual adhesion between separators can be reduced. The lower limit of the inorganic filler content in the adhesive layer is not particularly limited, and may be, for example, 0% by weight or more, more than 0% by weight, 10% by weight or more, 20% by weight or more, or 33% by weight or more. From the viewpoint of air permeability, the inorganic filler content in the adhesive layer is preferably 50% by weight or more.
[0024] [Method of manufacturing adhesive layer] The adhesive layer can be formed using a coating liquid obtained by dissolving or dispersing the resin component constituting the adhesive layer in a solvent. Also, the adhesive layer containing the resin component and the inorganic filler can be formed using a coating liquid obtained by dissolving or dispersing the resin component in a solvent and dispersing the inorganic filler.
[0025] The solvent may be a solvent that dissolves the resin component. The solvent may be a dispersion medium that disperses the resin component or the inorganic filler. Examples of the method for forming the coating liquid include a mechanical stirring method, an ultrasonic dispersion method, a high-pressure dispersion method, and a media dispersion method.
[0026] Examples of methods for forming the adhesive layer include a method in which the coating liquid is directly applied to the surface of a substrate and then the solvent is removed; a method in which the coating liquid is applied to a suitable support and then the solvent is removed to form the adhesive layer, the adhesive layer and the substrate are pressure-bonded together, and then the substrate is peeled off; a method in which the coating liquid is applied to a suitable support and then the substrate is pressure-bonded to the coating surface, and then the substrate is peeled off and then the solvent is removed; and a method in which the substrate is dip-coated by immersing it in the coating liquid and then the solvent is removed.
[0027] The solvent is preferably a solvent that does not adversely affect the substrate, dissolves the resin component uniformly and stably, and disperses the inorganic filler uniformly and stably. Examples of the solvent include one or more solvents selected from the group consisting of N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, acetone, water, and the like.
[0028] The coating liquid may appropriately contain a dispersant, a plasticizer, a surfactant, a pH adjuster, and the like as components other than the resin component and the inorganic filler.
[0029] The coating liquid can be applied to the substrate by any conventional method. Specific examples of the method include a gravure coater method, a dip coater method, a bar coater method, and a die coater method.
[0030] When the coating liquid contains an aramid resin, the aramid resin can be precipitated by applying moisture to the coating surface, thereby forming the adhesive layer.
[0031] Examples of a method for removing the solvent from the coating liquid applied to the substrate include a method for removing the solvent from a coating film, which is a film of the coating liquid, by ventilation drying, heat drying, or the like.
[0032] In addition, by changing the amount of the solvent in the coating liquid, the porosity and average pore size of the resulting adhesive layer can be adjusted.
[0033] A suitable solid content concentration of the coating liquid may vary depending on the type of inorganic filler, but is generally preferably more than 3% by weight and not more than 40% by weight.
[0034] The coating shear rate when the coating liquid is applied onto the substrate may vary depending on the type of inorganic filler, but is generally preferably 2 (1 / s) or more, and more preferably 4 (1 / s) to 50 (1 / s).
[0035] [2. Laminated separator] The laminated separator according to one embodiment of the present invention includes a polyolefin porous film and an adhesive layer. The laminated separator may optionally include a heat-resistant layer on one or both sides of the polyolefin porous film.
[0036] As shown in FIG. 1, in one embodiment, the laminate separator 4a includes a polyolefin porous film 1, a heat-resistant layer 2 provided on one side of the polyolefin porous film 1, and an adhesive layer 3a on the surface of the heat-resistant layer that is not in contact with the polyolefin porous film 1. The heat-resistant layer 2 may be a layer mainly composed of a heat-resistant resin, and may contain a filler or the like. The heat-resistant resin and the filler described in Section [1] can be used. The adhesive layer 3a may be a heat-resistant adhesive layer or a simple adhesive layer.
[0037] As shown in Fig. 2, in one embodiment, the laminated separator 4b includes a polyolefin porous film 1 and an adhesive layer 3b provided on one side of the polyolefin porous film 1. The adhesive layer 3b may be a heat-resistant adhesive layer or a simple adhesive layer. In order to impart a heat-resistant function to the laminated separator 4b, the adhesive layer 3b is preferably a heat-resistant adhesive layer.
[0038] 1, a heat-resistant layer and / or an adhesive layer may be laminated on the surface of the polyolefin porous film 1 on which the heat-resistant layer 2 is not laminated. In FIG. 2, a heat-resistant layer and / or an adhesive layer may be laminated on the surface of the polyolefin porous film 1 on which the adhesive layer 3b is not laminated, although not shown.
[0039] In this specification, the polyolefin porous film is also referred to as a "polyolefin-based substrate", and is a substrate mainly composed of a polyolefin-based resin. "Mainly composed of a polyolefin-based resin" means that the ratio of the polyolefin-based resin in the substrate is 50% by weight or more, preferably 90% by weight or more, and more preferably 95% by weight or more of the total material constituting the substrate. The polyolefin-based substrate is mainly composed of a polyolefin-based resin and has many interconnected pores inside, allowing gas and liquid to pass from one side to the other side.
[0040] The polyolefin has a weight average molecular weight of 5×10 5 ~15×10 6 In particular, it is more preferable that the polyolefin contains a high molecular weight component having a weight average molecular weight of 1,000,000 or more, since this improves the strength of the laminate separator for a nonaqueous electrolyte secondary battery according to one embodiment of the present invention.
[0041] The polyolefin may be, for example, a homopolymer or a copolymer obtained by polymerizing monomers such as ethylene, propylene, 1-butene, 4-methyl-1-pentene, and 1-hexene.
[0042] Examples of the homopolymer include polyethylene, polypropylene, and polybutene, and examples of the copolymer include an ethylene-propylene copolymer.
[0043] Among these, polyethylene is more preferable as the polyolefin because it can prevent the flow of excessive current at a lower temperature. Note that "preventing the flow of excessive current" is also called "shutdown."
[0044] Examples of the polyethylene include low-density polyethylene, high-density polyethylene, linear polyethylene (ethylene-α-olefin copolymer), ultra-high molecular weight polyethylene having a weight-average molecular weight of 1,000,000 or more, etc. Among these, the polyethylene is more preferably ultra-high molecular weight polyethylene having a weight-average molecular weight of 1,000,000 or more.
[0045] The basis weight of the substrate can be appropriately determined in consideration of the strength, film thickness, weight, and handleability. However, in order to increase the weight energy density and volume energy density of the nonaqueous electrolyte secondary battery, the basis weight is preferably 2 to 20 g / m 2 is preferably 2 to 12 g / m 2 More preferably, the thickness is 3 to 10 g / m 2 It is even more preferable that:
[0046] The air permeability of the substrate is preferably 30 to 500 s / 100 mL, more preferably 50 to 300 s / 100 mL, in terms of Gurley value. When the substrate has an air permeability within the above range, the substrate can obtain sufficient ion permeability.
[0047] The porosity of the substrate is preferably 20 to 80% by volume, and more preferably 30 to 75% by volume, in order to increase the amount of electrolyte retained and to obtain the function of reliably preventing the flow of excessive current at lower temperatures.
[0048] In addition, the pore size of the pores in the substrate is preferably 0.3 μm or less, and more preferably 0.14 μm or less, so as to obtain sufficient ion permeability and prevent particles from entering the positive electrode and negative electrode.
[0049] The lower limit of the thickness of the substrate is preferably 4 μm or more, more preferably 5 μm or more, and even more preferably 6 μm or more. The upper limit of the thickness of the substrate is preferably 29 μm or less, more preferably 20 μm or less, and even more preferably 15 μm or less. Examples of combinations of the lower limit and upper limit of the thickness of the substrate include 4 to 29 μm, 5 to 20 μm, and 6 to 15 μm.
[0050] [Manufacturing method of laminated separator] The method for producing the polyolefin-based substrate can be, for example, the following method. That is, first, a polyolefin-based resin, a pore-forming agent such as an inorganic filler or a plasticizer, and optionally an antioxidant, etc. are kneaded to obtain a polyolefin-based resin composition. Then, the polyolefin-based resin composition is extruded to prepare a sheet-shaped polyolefin-based resin composition. Then, the pore-forming agent is removed from the sheet-shaped polyolefin-based resin composition with an appropriate solvent. Then, the polyolefin-based resin composition from which the pore-forming agent has been removed is stretched to produce a polyolefin-based substrate.
[0051] The inorganic filler is not particularly limited, and examples thereof include inorganic fillers, specifically calcium carbonate, etc. The plasticizer is not particularly limited, and examples thereof include low molecular weight hydrocarbons such as liquid paraffin.
[0052] The method for producing the polyolefin-based substrate can include, for example, a method including the steps described below.
[0053] (i) a step of kneading ultra-high molecular weight polyethylene having a weight average molecular weight of 1 million or more, low molecular weight polyethylene having a weight average molecular weight of 10,000 or less, a pore-forming agent such as calcium carbonate or a plasticizer, and an antioxidant to obtain a polyolefin-based resin composition, (ii) a step of gradually cooling the obtained polyolefin-based resin composition and forming a sheet, (iii) a step of removing the pore-forming agent from the obtained sheet with an appropriate solvent, and (iv) a step of stretching the sheet from which the pore-forming agent has been removed at an appropriate stretch ratio.
[0054] In the method for producing an adhesive layer described in Section [1], if the substrate is a polyolefin porous film, the above-mentioned laminated separator can be produced.
[0055] [Physical properties of laminated separator] The adhesive strength between the laminated separator and the electrode (preferably the positive electrode) is preferably 0.5 N / m or more. If the adhesive strength is within the above range, it can be said that the adhesive layer functions sufficiently. For a specific method for measuring the adhesive strength, please refer to the examples of this application.
[0056] The laminate separator preferably has a heat shape retention rate in the MD direction of 90% or more. In this specification, the term "heat shape retention rate" refers to a parameter that indicates the degree to which an object can maintain its pre-heated shape when heated. For a specific method for measuring the heat shape retention rate, see the examples of this application. If the heat shape retention rate is within the above range, it can be said to have excellent heat resistance.
[0057] 3. Non-aqueous electrolyte secondary battery components and non-aqueous electrolyte secondary batteries The nonaqueous electrolyte secondary battery member according to one embodiment of the present invention may have a positive electrode, the above-mentioned adhesive layer for nonaqueous electrolyte secondary batteries, and a negative electrode laminated in this order. Alternatively, the nonaqueous electrolyte secondary battery member according to one embodiment of the present invention may have a positive electrode, the above-mentioned separator, and a negative electrode laminated in this order. The nonaqueous electrolyte secondary battery according to one embodiment of the present invention includes the above-mentioned adhesive layer for nonaqueous electrolyte secondary batteries, the above-mentioned separator, or the above-mentioned nonaqueous electrolyte secondary battery member.
[0058] The shape of the nonaqueous electrolyte secondary battery is not particularly limited, and may be a thin plate (paper) type, a disk type, a cylinder type, a prismatic type such as a rectangular parallelepiped, etc. The nonaqueous electrolyte secondary battery is, for example, a nonaqueous electrolyte secondary battery that obtains electromotive force by doping and dedoping lithium, and includes a nonaqueous electrolyte secondary battery member in which a positive electrode, the above-mentioned separator, and a negative electrode are laminated in this order. Note that the components of the nonaqueous electrolyte secondary battery other than the above-mentioned separator are not limited to the components described below.
[0059] The nonaqueous electrolyte secondary battery generally has a structure in which a battery element, in which a negative electrode and a positive electrode are opposed to each other via the separator described above and an electrolyte is impregnated in the structure, is enclosed in an exterior material. Note that the term "doping" refers to occlusion, support, adsorption, or insertion, and refers to the phenomenon in which lithium ions enter the active material of an electrode such as a positive electrode.
[0060] Since the nonaqueous electrolyte secondary battery member includes the above-mentioned separator, when the nonaqueous electrolyte secondary battery member is incorporated therein, the occurrence of micro-short circuits in the nonaqueous electrolyte secondary battery can be suppressed and the safety of the battery can be improved. Furthermore, since the nonaqueous electrolyte secondary battery includes the above-mentioned separator, the occurrence of micro-short circuits is suppressed and the battery has excellent safety.
[0061] [Positive electrode] The positive electrode in one embodiment of the present invention is not particularly limited as long as it is generally used as a positive electrode of a non-aqueous electrolyte secondary battery. For example, a positive electrode sheet having a structure in which an active material layer containing a positive electrode active material and a binder is formed on a positive electrode current collector can be used as the positive electrode. The active material layer may further contain a conductive agent and / or a binder.
[0062] The positive electrode active material may be, for example, a material capable of doping and dedoping lithium ions, specifically, a lithium composite oxide containing at least one transition metal such as V, Mn, Fe, Co, or Ni.
[0063] Examples of the conductive agent include carbonaceous materials such as natural graphite, artificial graphite, cokes, carbon black, pyrolytic carbons, carbon fibers, and organic polymer compound sintered bodies. The conductive agent may be used alone or in combination of two or more kinds.
[0064] Examples of the binder include fluorine-based resins such as polyvinylidene fluoride (PVDF), acrylic resins, and styrene-butadiene rubber. The binder also functions as a thickener.
[0065] Examples of the positive electrode current collector include conductors such as Al, Ni, stainless steel, etc. Among them, Al is more preferable because it is easy to process into a thin film and is inexpensive.
[0066] Examples of methods for producing a positive electrode sheet include a method of pressurizing and molding a positive electrode active material, a conductive agent, and a binder on a positive electrode current collector; a method of forming a paste of a positive electrode active material, a conductive agent, and a binder using an appropriate organic solvent, applying the paste to a positive electrode current collector, drying the paste, and then applying pressure to adhere the paste to the positive electrode current collector.
[0067] [Negative electrode] The negative electrode in one embodiment of the present invention is not particularly limited as long as it is generally used as a negative electrode of a non-aqueous electrolyte secondary battery. For example, a negative electrode sheet having a structure in which an active material layer containing a negative electrode active material and a binder is formed on a negative electrode current collector can be used as the negative electrode. The active material layer may further contain a conductive agent and / or a binder.
[0068] The negative electrode active material may be, for example, a material capable of doping and dedoping lithium ions. Examples of such materials include carbonaceous materials. Examples of carbonaceous materials include natural graphite, artificial graphite, cokes, carbon black, and pyrolytic carbons.
[0069] The negative electrode current collector may be made of, for example, Cu, Ni, stainless steel, etc. Cu is more preferred because it is difficult to form an alloy with lithium and is easy to process into a thin film.
[0070] Examples of the method for producing the negative electrode sheet include a method of pressurizing and molding the negative electrode active material on the negative electrode current collector, a method of forming the negative electrode active material into a paste using an appropriate organic solvent, applying the paste to the negative electrode current collector, drying, and then pressing to fix the paste to the negative electrode current collector, etc. The paste preferably contains the conductive agent and the binder.
[0071] [Nonaqueous electrolyte] The non-aqueous electrolyte in one embodiment of the present invention is not particularly limited as long as it is a non-aqueous electrolyte generally used in non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries. As the non-aqueous electrolyte, for example, a non-aqueous electrolyte obtained by dissolving a lithium salt in an organic solvent can be used. As the lithium salt, for example, LiClO4, LiPF6, LiAsF6, LiSbF6, LiBF4, LiCF3SO3, LiN(CF3SO2)2, LiC(CF3SO2)3, Li2B 10 Cl 10 , lithium salts of lower aliphatic carboxylates, LiAlCl4, etc. The lithium salts may be used alone or in combination of two or more.
[0072] Examples of the organic solvent constituting the nonaqueous electrolyte include carbonates, ethers, esters, nitriles, amides, carbamates, sulfur-containing compounds, and fluorine-containing organic solvents obtained by introducing a fluorine group into these organic solvents. The organic solvents may be used alone or in combination of two or more.
[0073] [Method for manufacturing non-aqueous electrolyte secondary battery] A conventionally known manufacturing method can be used as the manufacturing method of the nonaqueous electrolyte secondary battery. For example, the positive electrode, the above-mentioned separator, and the negative electrode are arranged in this order to form the nonaqueous electrolyte secondary battery member. Next, the nonaqueous electrolyte secondary battery member is placed in a container that will become the housing of the nonaqueous electrolyte secondary battery. Furthermore, the container is filled with a nonaqueous electrolyte, and then sealed while reducing the pressure. This allows the nonaqueous electrolyte secondary battery to be manufactured. EXAMPLES
[0074] [Evaluation method for evaluation items] [Adhesive strength] The evaluation was carried out according to the following procedure. 1. The laminated separator obtained in the examples or comparative examples was cut out (length: 80 mm x width: 27 mm). 2. The cut laminate separator was placed on a release paper with the adhesive side facing up, and the release paper was then placed on a polyurethane sheet. 3. A positive electrode (length: 50 mm × width: 20 mm), a glass epoxy plate, release paper, and a polyurethane sheet were laminated in this order on the laminated separator, thereby obtaining a laminate in which the polyurethane sheet, release paper, polyethylene film, adhesive layer, positive electrode, glass epoxy plate, release paper, and polyurethane sheet were laminated in this order. 4. The laminate was preheated by pressing at 90°C, 1 MPa, for 30 seconds, and then pressed at 90°C, 6 MPa, for 10 seconds to bond the laminate. 5. The polyethylene film, adhesive layer, positive electrode and glass epoxy plate were taken out, and the positive electrode and glass epoxy plate were fixed together with double-sided tape. 6. The edge of the laminated separator was pulled so that the angle between the positive electrode and the laminated separator was 180°, and the maximum tensile strength at which it was peeled off was recorded as G1 (N). 7. The value obtained by dividing the G1 value by the width of the positive electrode (0.02 m) was determined as the adhesive strength (N / m) between the adhesive layer and the positive electrode.
[0075] [Heating shape retention rate] The measurement was carried out according to the following procedure. 1. The laminate separator obtained in the examples or comparative examples was cut into a square sample measuring 80 mm x 80 mm, with each side of the square parallel to either the MD or TD. 2. A line was drawn on the inside of the perimeter of the 80mm x 80mm, and a 60mm x 60mm square was drawn. At this time, the lines were drawn so that each side of the square was parallel to either the MD or TD direction. The square was drawn on the surface of the adhesive layer. 3. The sample sandwiched between pieces of paper was placed in an oven heated to 130°C and left to stand for 1 hour. 4. The sample was removed from the oven. The length of the sides of the square drawn on the sample was measured with a digital caliper. 5. The deformation in the MD direction of the sample after heating is called D MDThis value was taken as the heat shape retention rate. MD is the length (mm) of a line parallel to the MD direction in a square drawn on the sample after heating.
[0076] In this specification, the term "MD direction" refers to the conveying direction in the production of a long film, and the term "TD direction" refers to the direction parallel to the surface of the long film and perpendicular to the MD direction.
[0077] [Synthesis Example 1: Synthesis of Polymer (1)] Polymer (1) was synthesized by the following procedure: Polymer (1) is a semi-aromatic polyamide having a hydrocarbon chain. 1. A 300 mL separable flask equipped with a stirring blade, a thermometer, a nitrogen inlet, and a powder addition port was thoroughly dried. 2. 193 g of N-methylpyrrolidone was placed in a flask. 2.83 g of hexamethylenediamine was added and allowed to dissolve completely for 1 hour. 3. The liquid temperature was cooled to 20° C. Then, 4.84 g of terephthalic acid dichloride was added and reacted for 1.5 hours. In this way, a solution 1 containing a polymer (1) obtained by a condensation reaction of hexamethylenediamine and terephthalic acid dichloride was obtained.
[0078] [Synthesis Example 2: Synthesis of Polymer (2)] Polymer (2) was synthesized by the following procedure: Polymer (2) is a semi-aromatic polyamide having a polyether chain. 1. A 300 mL separable flask equipped with a stirring blade, a thermometer, a nitrogen inlet, and a powder addition port was thoroughly dried. 2. 196 g of N-methylpyrrolidone was placed in a flask. 1.77 g of 1,2-bis(2-aminoethoxy)ethane was added and allowed to dissolve completely for 1 hour. 3. The liquid temperature was cooled to 20°C. Then, 2.38 g of terephthalic acid dichloride was added and reacted for 1.5 hours. In this way, a solution 2 containing a polymer (2) obtained by the condensation reaction of 1,2-bis(2-aminoethoxy)ethane and terephthalic acid dichloride was obtained.
[0079] [Synthesis Example 3: Synthesis of polymer (3)] Polymer (3) was synthesized by the following procedure: Polymer (3) is an aliphatic polyamide having a hydrocarbon chain and a polyether chain. 1. A 300 mL separable flask equipped with a stirring blade, a thermometer, a nitrogen inlet, and a powder addition port was thoroughly dried. 2. 142.5 g of N-methylpyrrolidone was placed in a flask, and the liquid temperature was raised to 40° C. 9.65 g of O,O'-bis(2-aminopropyl)polypropylene glycol-block-polyethylene glycol-block-polypropylene glycol (Jeffamine (registered trademark) ED-2003, manufactured by HUNTSMAN) was added, and completely dissolved over one hour. 3. The liquid temperature was cooled to 20°C. Then, 0.85 g of hexamethylene diisocyanate was added and reacted for 1.5 hours. In this way, a solution 3 containing a polymer (3) obtained by a condensation reaction of O,O'-bis(2-aminopropyl)polyethylene glycol-block-polyethylene glycol-block-polyethylene glycol and hexamethylene diisocyanate was obtained.
[0080] [Synthesis Example 4: Synthesis of polymer (4)] Polymer (4) was synthesized according to the following procedure: Polymer (4) is a wholly aromatic polyamide. 1. A 500 mL separable flask equipped with a stirring blade, a thermometer, a nitrogen inlet, and a powder addition port was thoroughly dried. 2. 470 g of N-methylpyrrolidone was placed in a flask, followed by 32 g of calcium chloride (dried at 200°C for 2 hours) and heating to 100°C. 3. After calcium chloride was completely dissolved, the temperature of the solution was returned to room temperature, and then 13.8 g of paraphenylenediamine was added and completely dissolved. 4. While maintaining the temperature of the solution at 20±2°C, a total of 25.3 g of terephthalic acid dichloride was added in three portions. 5. The temperature of the obtained solution was kept at 20±2° C. and the solution was aged for 1 hour to obtain a solution 4 containing a polymer (4).
[0081] Example 1 1. An adhesive layer having a weight ratio of polymer (1):polymer (4) of 50:50 was prepared. Specifically, the solutions synthesized in Synthesis Examples 1 and 4 were mixed so that the weight ratio of polymer (1):polymer (4) was 50:50. 100 parts by weight of aluminum oxide (average particle size: 0.013 μm) was added to 100 parts by weight of the total amount of resin contained in this mixed solution. The resulting mixture was diluted with N-methylpyrrolidone and uniformly dispersed by a pressure type disperser to obtain coating solution (1). The solid content concentration of coating solution (1) was 5% by weight. 2. Polyethylene porous film (thickness: 11 μm, weight per unit area: 6.4 g / m 2 ) was coated with the coating liquid (1). In this way, a coated object 1 was obtained. 3. The coated product 1 obtained in step 2 was treated in an oven at 50° C. and humidity of 70% for 1 minute, thereby forming an adhesive layer 1 on the polyethylene porous film. 4. The adhesive layer 1 was washed with water and dried to obtain a laminated separator 1 provided with the adhesive layer 1.
[0082] Example 2 A laminated separator 2 was obtained in the same manner as in Example 1, except that the polymer (2) obtained in Synthesis Example 2 was used instead of the polymer (1).
[0083] Example 3 1. To the solution 4 synthesized in Synthesis Example 4, 100 parts by weight of aluminum oxide (average particle size: 0.013 μm) was added relative to 100 parts by weight of the total amount of polymer (4) contained in this solution 4. The resulting mixture was diluted with N-methylpyrrolidone and uniformly dispersed using a pressure type disperser to obtain coating liquid (3). The solid content concentration of coating liquid (3) was 5% by weight. 2. Polyethylene porous film (thickness: 11 μm, weight per unit area: 6.4 g / m 2 ) was coated with the coating liquid (3). In this way, a coated object 3 was obtained. 3. The coated product 3 obtained in step 2 was treated in an oven at 50° C. and humidity of 70% for 1 minute, thereby forming a heat-resistant layer 3 on the polyethylene porous film. 4. The coated material 3 was washed with water and dried to remove the solvent, thereby obtaining a separator 3 having a heat-resistant layer 3. 5. A coating liquid in which the solid content concentration of solution 3 synthesized in Synthesis Example (3) was adjusted to 10% was applied to the surface of separator 3 obtained in step 4 on which heat-resistant layer 3 was formed. 6. The coating obtained in step 5 was dried for 30 minutes in an oven at 80° C. As a result, a laminated separator 3 was obtained in which a heat-resistant layer 3 was formed on one side of the polyolefin porous film and an adhesive layer was further formed on the heat-resistant layer 3.
[0084] Comparative Example 1 A laminated separator C1 was obtained by carrying out the same operations as in Example 1, except that the weight ratio of polymer (1):polymer (4) was changed to 0:100.
[0085] 〔result〕 The results are shown in Table 1. [Table 1]
[0086] As can be seen from Table 1, the laminate separator C1 did not adhere to the positive electrode. In contrast, the laminate separator 1 to 3 were able to adhere to the positive electrode. This is presumably because the laminate separators 1 to 3 have an adhesive layer containing a flexible chain polymer. Furthermore, the heat resistance of the laminate separators 1 to 3 was comparable to that of Comparative Example 1, which corresponds to the prior art. [Industrial Applicability]
[0087] The present invention can be used for non-aqueous electrolyte secondary batteries and the like. [Explanation of symbols]
[0088] 1:Polyolefin porous film 2: Heat resistant layer 3a, 3b: Adhesive layer 4a, 4b: Laminated separator
Claims
1. An adhesive layer for a non-aqueous electrolyte secondary battery comprising a flexible chain polymer, The flexible chain polymer is a polymer having a carbonyl group in its main chain and a flexible chain in its structure, The flexible chain is a structure that is not entirely aromatic. Adhesive layer for non-aqueous electrolyte secondary batteries.
2. 2. The adhesive layer for a non-aqueous electrolyte secondary battery according to claim 1, wherein the carbonyl group is contained in at least one bond selected from the group consisting of an amide bond, an ester bond, an imide bond, a urethane bond and a urea bond.
3. 2. The adhesive layer for a non-aqueous electrolyte secondary battery according to claim 1, wherein the flexible chain polymer is at least one selected from the group consisting of semi-aromatic polyamide, aliphatic polyamide, semi-aromatic polyurea, aliphatic polyurea, semi-aromatic polyurethane, and aliphatic polyurethane.
4. 2. The adhesive layer for a non-aqueous electrolyte secondary battery according to claim 1, wherein the flexible chain polymer is present in an amount of 20 to 100% by weight, with the total weight of the resin contained in the adhesive layer being 100% by weight.
5. The adhesive layer for a non-aqueous electrolyte secondary battery according to claim 1 , further comprising a heat-resistant resin.
6. A laminate separator for a non-aqueous electrolyte secondary battery, comprising a heat-resistant layer on one or both sides of a polyolefin porous film, and further comprising the adhesive layer for a non-aqueous electrolyte secondary battery according to claim 1 laminated on the surface of the heat-resistant layer that is not in contact with the polyolefin porous film.
7. 13. A laminate separator for a non-aqueous electrolyte secondary battery, comprising the adhesive layer for a non-aqueous electrolyte secondary battery according to claim 1 laminated on one or both sides of a polyolefin porous film.
8. A positive electrode and The adhesive layer for a non-aqueous electrolyte secondary battery according to claim 1 ; A negative electrode; are laminated in this order.
9. A positive electrode and The laminate separator for a nonaqueous electrolyte secondary battery according to claim 6 ; A negative electrode; are laminated in this order.
10. A positive electrode and The laminate separator for a nonaqueous electrolyte secondary battery according to claim 7 ; A negative electrode; are laminated in this order.
11. A nonaqueous electrolyte secondary battery comprising the adhesive layer for a nonaqueous electrolyte secondary battery according to any one of claims 1 to 5, the laminate separator for a nonaqueous electrolyte secondary battery according to claim 6 or 7, or the member for a nonaqueous electrolyte secondary battery according to any one of claims 8 to 10.
Citation Information
Patent Citations
Partition wall panel
JP2006299612A